Domain‐specific development of face memory but not face perception. Issue 1 (7th October 2013) - Weigelt, Sarah; Koldewyn, Kami; Dilks, Daniel D.; Balas, Benjamin; McKone, Elinor; Kanwisher, Nancy
Abstract How does the remarkable human ability for face recognition arise over development? Competing theories have proposed either late maturity (beyond 10 years) or early maturity (before 5 years), but have not distinguished between perceptual and memory aspects of face recognition. Here, we demonstrate a perception–memory dissociation. We compare rate of development for (adult, human) faces versus other social stimuli (bodies), other discrete objects (cars), and other categories processed in discrete brain regions (scenes, bodies), from 5 years to adulthood. For perceptual discrimination, performance improved with age at the same rate for faces and all other categories, indicating no domain‐specific development. In contrast, face memory increased more strongly than non‐face memory, indicating domain‐specific development. The results imply that each theory is partly true: the late maturity theory holds for face memory, and the early maturity theory for face perception.